2003
DOI: 10.1093/hsw/28.3.174
|View full text |Cite
|
Sign up to set email alerts
|

Abuse and Neglect of Clients in Agency-Based and Consumer-Directed Home Care

Abstract: Because a growing number of Americans receive long-term care at home, social workers face new challenges in referring clients to either agency-based or consumer-directed care models. Traditional agency-based home care often is considered safer for disabled clients because workers are professionally trained and monitored; newer, client-directed home care models offer more autonomy and flexibility. This study examined differences in worker abuse and neglect of clients across agency and consumer-directed models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…A third explicitly included women with both physical and intellectual disabilities, as well as women with physical disabilities alone. Two studies [Matthias and Benjamin, 2003;Oktay and Tompkins, 2004] examined maltreatment perpetrated by personal assistants, and one [Bryen et al, 2003] studied maltreatment experienced by users of augmentative and alternative communication. Although these studies may have incidentally included individuals with ID, they focused primarily on physical disabilities and were based on self-report surveys that may have precluded participation by people with significant cognitive impairments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A third explicitly included women with both physical and intellectual disabilities, as well as women with physical disabilities alone. Two studies [Matthias and Benjamin, 2003;Oktay and Tompkins, 2004] examined maltreatment perpetrated by personal assistants, and one [Bryen et al, 2003] studied maltreatment experienced by users of augmentative and alternative communication. Although these studies may have incidentally included individuals with ID, they focused primarily on physical disabilities and were based on self-report surveys that may have precluded participation by people with significant cognitive impairments.…”
Section: Resultsmentioning
confidence: 99%
“…In studies of personal assistant maltreatment, the results of Matthias and Benjamin [2003] and Oktay and Tompkins [2004] provide some indication that this type of maltreatment may be even more prevalent than Powers et al [2002] found either for women with both ID and physical disabilities or for women with physical disabilities alone. However, it is difficult to compare these studies given the different sampling methodologies utilized and the fact that studied lifetime prevalence of maltreatment from any personal assistants, while Oktay and Tompkins studied maltreatment from current personal assistants, and Matthias and Benjamin studied personal assistant maltreatment that had occurred within the past year.…”
Section: Comparing People With Id To People With Other Disabilitiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Research into the context where interpersonal violence against people with disabilities occurs has focused largely on institutional or congregate settings (Cambridge, 1999;Crossmaker, 1991;McCarthy & Thompson, 1996) and private residences whereby the perpetrator is an intimate partner (Brownridge, 2006;Coker et al, 2005;Smith, 2007), family member, or paid care provider (Matthias & Benjamin, 2003;Oktay & Tompkins, 2004;Powers et al, 2002;Saxton et al, 2001;Saxton et al, 2006). Little attention has been paid to geographic context, particularly the rural community context, and relevance for understanding interpersonal violence against people with disabilities.…”
mentioning
confidence: 99%